Little robotic autos that can. (IEEE spectrum)
Researchers at the Institute for Mechatronic Systems (IMS, Winterthur, Switzerland), have developed a car that can find a parking space by itself and parallel-park in a single go without bumping into anything. For their test model, Charles Brom, head of IMS, and his team chose a DaimlerChrysler gasoline-powered Smart car on the grounds that it already contained so-called drive-by-wire elements that support autonomous parking. These include an electronic gear shift and a CANbus (controller area network bus) system. But why worry about parking at all? The city of Cardiff, Wales, has unveiled a prototype of an automatically controlled personal taxi system that runs on its own guideway network. The ULTra PRT (urban light transport personal rapid transit) system will take people where they want, when they want, and at 40 km/h